Teacher-Students’ Classroom Interaction in Teaching Grammar with Interactive Learning Approach - Sholikhah, Yayang Imroatus; Saefullah, Hilmansyah (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
In this study, classroom interactions during an interactive grammar learning process are analyzed. It attempts to explore the teacher’s interaction strategies in teaching grammar using an interactive learning approach. Based on observation analysis using the Flanders Interaction Analysis Category (FIAC) to an English teacher and four volunteers learning English grammar, this study revealed that the teacher’s interaction strategies in teaching grammar using interactive learning approach include activities like asking question, giving encouragement or praise, lecturing, and giving directions. Based on this study, the interactive learning approach can encourage students to participate in sharing their ideas during the learning process.